STUDIES ON POST-HARVEST DISEASES OF APRICOT AND CHEMICAL CONTROL OF WHISKERS ROT - AND K. K. JINDAL, R. C. SHARMA, J. L. KAUL (Indian Phytopathology, 2002)
Seven post-harvest diseases of apricot were .recorded causing heavy losses during storage and marketing. Amongst these, whiskers rot was the most prevalent and severe. Storage of apricots at 5Â°C effectively reduced the losses due to fungal pathogens. At this temperature,. only Penicillium expansum could infect the fruit. Six fungicides were tested as postinoculation dip treatment to ascertain their effect on the spoilage of apricots due to Rhizopus stolonijer. Only dichloran dip treatment provided complete protection against R. stoioniier infection.